Preparing Pre-Service Teachers to Use Visual Representations as Strategy to Solve Mathematics Problems: What Did They Learn?. (November 2021) - van Garderen, Delinda; Scheuermann, Amy; Sadler, Kate; Hopkins, Stephanie; Hirt, Stacy M.
Recognizing the multiple interacting layers of pedagogical content knowledge, in this article, we present the findings from a study that examined the extent to which participation in case-based instruction about self-generated visual representations (VRs) supported special education pre-service teachers ( N = 25) in enhancing their (a) knowledge of VRs, specifically what and how to teach, as a strategy for solving mathematics problems, and (b) applied instructional practices, specifically analysis of student knowledge and instructional planning, about VRs for students with disabilities (SWDs) to solve mathematics problems. The data revealed that case-based instruction about VRs in a special education mathematics methods course enriched pre-service teachers personal understanding about VRs and their ability to target SWDs learning needs regarding VRs. Implications for pre-service teacher preparation and research are provided.